Pengaruh Jumlah Traffic Terhadap Situation Awareness Personel Pemandu Lalu Lintas Udara di Perum LPPNPI Cabang Tanjungpinang - Putri Permata Ridayanti; Rany Adiliawijaya; Martha Saulina (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
The purpose of this research to know the effect of the amount of traffic in air traffic control personnel’s situation awareness at Perum LPPNPI Tanjungpinang branch. The method used in this research is quantitative research and data collected used documentation and questionnare. As for the population in this research are 52 Air Traffic Controller personnels of Tanjungpinang Approach Control Unit. The result shows positive effect and parallel between the amount of traffic are controlled and air traffic controller’s situation awareness. Positive effect shows decreasing the amount of traffic are controlled so air traffic controller’s situation awareness will be decreasing and vice versa. Determination coefficient is 36% and the rest is determined by the other factors. The regression equation test is Y = 20,451 + 0,570 X.